The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.5187/jast.2022.e22
|View full text |Cite
|
Sign up to set email alerts
|

Mid-infrared (MIR) spectroscopy for the detection of cow’s milk in buffalo milk

Abstract: In Italy, buffalo mozzarella is a largely sold and consumed dairy product. The fraudulent adulteration of buffalo milk with cheaper and more available milk of other species is very frequent. In the present study, Fourier transform infrared spectroscopy (FTIR), in combination with multivariate analysis by partial least square (PLS) regression, was applied to quantitatively detect the adulteration of buffalo milk with cow milk by using a fully automatic equipment dedicated to the routine analysis of the milk com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Buffalo milk had the highest total solids, followed by camel milk and goat milk, while cow milk had the lowest. These data show the higher content of fat in buffalo milk, goat milk, and camel milk than in cow milk, and are in agreement with those reported in previous studies [6,18]. According to the spectra, a region of approximately 2900 cm −1 provided information about the fat molecules [29], with buffalo milk having the highest peak, followed by goat milk and camel milk, with cow milk having the lowest peak.…”
Section: Quality Parameter Evaluation and Ftir Spectral Characteristi...supporting
confidence: 91%
See 1 more Smart Citation
“…Buffalo milk had the highest total solids, followed by camel milk and goat milk, while cow milk had the lowest. These data show the higher content of fat in buffalo milk, goat milk, and camel milk than in cow milk, and are in agreement with those reported in previous studies [6,18]. According to the spectra, a region of approximately 2900 cm −1 provided information about the fat molecules [29], with buffalo milk having the highest peak, followed by goat milk and camel milk, with cow milk having the lowest peak.…”
Section: Quality Parameter Evaluation and Ftir Spectral Characteristi...supporting
confidence: 91%
“…Therefore, MIRS technology may be an ideal solution for detecting and quantifying adulteration (e.g., adulteration with cow milk or water) in these milks. Several studies have also demonstrated the effectiveness and potential of MIRS in predicting adulteration in buffalo milk [7,18], goat milk [3,7], and camel milk [19,20], but few studies report the application of MIRS in predicting water adulteration in buffalo milk, goat milk, and camel milk.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the commercial milk already passed to technological operation (heat treatments, fat separation, homogenization); thus, it would be more representative of real fraud to mix the different types of milk before any unit operation. This is what was done by Spina et al [83], who described in detail the farmers, the breeds, and the sampling period and batches. Furthermore, they strengthened their experimental plan by planning a randomized pairing of cow and buffalo milk to obtain 17 adulteration levels.…”
Section: Sampling Strategiesmentioning
confidence: 69%
“…MIR spectroscopy is also widely used coupled with PLS regression to detect and quantify adulterants in different milk samples. In several works, MIR was used to quantify the amount of cow's milk in more expensive milk types: buffalo [83,84], goat [85], and horse [86]. It was used to analyze coconut milk samples adulterated with water [87].…”
Section: Regressionmentioning
confidence: 99%
See 1 more Smart Citation